2017
DOI: 10.1177/2309499017713917
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spondylolysis: A report of four cases from two generations of a family

Abstract: Spondylolysis is a major cause of back pain in children and adolescents. The prevalence of spondylolysis depends on the sex, race, and congenital abnormality. These biases suggest hereditary predisposition as an etiology of spondylolysis. However, no conclusive evidence still exists regarding the inheritance for spondylolysis. Herein, we report rare cases with familial occurrence of lumbar spondylolysis. In two generations of a Japanese family, three brothers including identical twins complained of back pain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
9
0
6
Order By: Relevance
“…However, compared with Western countries, 2 , 11 13 there is less evidence of familial lumbar spondylolysis from Asian countries. 14 17 A previous study reported L5 spondylolysis with spina bifida from the fourth lumbar vertebra (L4) to the second sacral vertebra (S2) in three brothers from the same Japanese family. 16 Similar to this report, our patients also showed obvious spina bifida, indicating a possible inherent genetic weakness of the pars that might facilitate stress fractures.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with Western countries, 2 , 11 13 there is less evidence of familial lumbar spondylolysis from Asian countries. 14 17 A previous study reported L5 spondylolysis with spina bifida from the fourth lumbar vertebra (L4) to the second sacral vertebra (S2) in three brothers from the same Japanese family. 16 Similar to this report, our patients also showed obvious spina bifida, indicating a possible inherent genetic weakness of the pars that might facilitate stress fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Современные исследователи, изучая спондилолиз, традиционно придерживаются двух основных теорий его происхождения и развития: врожденной [9,16,17] и приобретенной [18][19][20][21][22]. Основоположником теории о врожденном происхождении принято считать Ф.л.…”
Section: материал и методыunclassified
“…В статье описывается случай диагностики патологии у трех родных братьев на уровне lIV и lV позвонков и у их отца, у которого на основании клинической симптоматики был диагностирован спондилолиз lIV и спондилолистез lIV и lV позвонков. По мнению авторов, частое развитие патологии в этой семье (у 4 из 6 человек, за исключением матери и сестры родных братьев) на уровне редко поражаемого спондилолизом lIV позвонка указывает на генетическую этиологию заболевания, в первую очередь на аутосомно-доминантное наследование [9].…”
Section: материал и методыunclassified
See 2 more Smart Citations